THE INFLUENCE OF HEAD MASTER’S CHARISMATIC LEADERSHIP AND TEACHER’S PERSONALITY TO TEACHER WORK ETHOS - Rusmiyati RUSMIYATI (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2019)
The purpose of this research was to find out the principal’s charismatic leadership influence and teacher’s personality on the teacher ethos in private Islamic integrated Junior High School Cimanggis, Depok. Validated and reliable questionnaires (using Pearson Product Moment and Cronbach Formula) were distributed to 126 sampled teachers out of population 184 teachers. Data were analyzed using path analysis (alpha .05). The study showed that there is direct and positive influences of: (1) the principal’s charismatic leadership on teacher work ethos indicated by path coefficient .128; (2) teacher personality on work ethos indicated by path coefficient .208 and (3) the principal’s charismatic leadership on teacher personality indicated by path coefficient .250.